(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
The article aims to reach an understanding of the scholarly work developed by Hegel and Friedrich Schlegel concerning the Philosophy of History, from the analysis of what is considered as a constant dispute between idealism and romanticism, in which the ideas of a systematic exposition, inherent to philosophy as science, as well as the rhetorical resort to irony and the confessional confrontation of Christianities following the Reformation and its universal history.